Floating door sign does not differentiate Parkinson's disease from essential tremor - Räty Valtteri; Eklund Mikael; Nuuttila Simo; Jaakkola Elina; Mäkinen Elina; Murtomäki Kirsi; Nojonen Tanja; Levo Reeta; Mertsalmi Tuomas; Joutsa Juho; Scheperjans Filip; Kaasinen Valtteri (Elsevier Ltd, 2025)
Diagnostic usefulness of the floating door sign was tested in 144 PD patients, 41 essential tremor patients and 38 controls. There were no differences in the presence of floating door sign between PD and ET patients. The sign does not seem to be a reliable differential diagnostic tool. © 2023 The Authors